Vulvar Basal Cell Carcinoma with Clitoral Involvement - Celik, Husnu; Gurates, Bilgin; Yavuz, Adem; Dogan, Zeynep; Cobanoglu, Bengu; Saral, Yunus (Acta Dermato-Venereologica, 2009)
[Abstract Not Available]